Adverse childhood experiences and homicide - Jones, Melissa (Routledge handbook of homicide studies, 2024)
Here, we present information regarding the prevalence and consequences of ACEs, review recent literature that shows an association between ACEs and violent behavior, and present evidence suggesting that both specific types of ACEs and the accumulation of ACEs during childhood are important risk factors for engaging in homicidal acts later in life. Because the research on ACEs and homicide is sparse, we tentatively conclude it is unlikely that the pathway from ACEs to homicide is direct and unmitigated. Instead, we suspect that there are multiple pathways that might lead from ACEs in childhood to homicide in adolescence and adulthood. These pathways likely involve several factors that mediate the ACEs-homicide association, such as adolescent problem behaviors; maladaptive personality traits, including an explosive temper, cruelty, and psychopathy; experiencing IPV; traumatic brain injuries; and impaired coping skills that diminish one’s ability to manage stress. Moreover, ACEs should be considered distal risk factors for homicide offending.